Ergonomi ditinjau dari Antropometri pada Interior Toko Makanan dan Kafe (Kasus: J.CO & MAKO Cake and Bakery di Summarecon Mall Serpong, Tangerang) - Fhanes Angelina; Jenniefer Christine; Avika Berliana; Alifia Wida Izzati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Pradita, 2026)
This study examines the application of ergonomics based on anthropometry in the interior design of J.CO & MAKO Cake and Bakery at Summarecon Mall Serpong. The research is grounded in the importance of furniture comfort in supporting user activities and enhancing spatial experience. A descriptive qualitative method was employed through field observation, furniture dimension measurement, and literature review. The analysis focuses on display units, coffee tables, stools, and circulation areas based on anthropometric standards by Panero and Zelnik. The findings indicate that display and circulation elements generally meet ergonomic standards, while coffee tables and stools are not fully compliant with anthropometric dimensions. These results highlight the importance of aligning furniture dimensions with human body measurements to improve comfort, safety, and efficiency. This study is expected to provide a reference for designing more ergonomic café and food retail interiors.